Yen Synchronization and Maastricht Convergence among the ASEAN-5, Japan and Korea - Wong, Kelly Kai Seng (2010)
In this thesis, the main objective is to investigate whether ASEAN-5+2 countries meet the conditions for creating an AMU with the yen as the currency unit. First, the results of BEKK-GARCH (1, 1) and the dynamic correlation coefficients show that only Singapore, Korea, and Thailand have the potential to adopt the yen as the regional currency unit. Second, the Maastricht criteria only have a significant impact on real GDP per capita growth for Japan, Korea, Singapore and the Philippines in the long term. In addition, the Maastricht criteria show that there were symmetry impacts on the growth of real GDP per capita for Japan, Korea, Singapore and the Philippines. Thus, only these four out of the seven countries (Japan, Korea, Singapore and the Philippines) appear to be potential candidates for establishing the AMU. Overall, the findings do not suggest the possibility of a formation of a full-fledged AMU by the ASEAN-5+2 countries. However, the formation of a sub-grouping of a few of the countries in the ASEAN-5+2 is more feasible, that is Japan, Singapore, and Korea. This is because these countries have higher institutional quality and fulfill the Maastricht treaty as well as being close in exchange rate regimes, and also have symmetrical economic behavior.